Digital Payment as Moderating Influence of Intellectual Capital on Business Performance - Retno Tri Handayani; Evana Andriani; Agung Subono; Affan Wazzar Achmad (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
MSMEs are the pillars of the economy in Indonesia. The role in employment absorption is also very large. However, this cannot be separated from the challenges that exist for the sustainability and success of an MSME. The aim of this research is to examine the influence of intellectual capital on business performance and the role of digital payments in moderating the influence of intellectual capital on business performance. The city of Kudus itself is proven to be an industrial city where many residents choose to work as businesspeople, so the object of this research is young entrepreneurs. The sample data processed in this research amounted to 110 respondents. The analysis tool used is SMART PLS. This type of research is quantitative research. The results of this research indicate that Intellectual Capital is not proven to have an effect on business performance. Digital payments have been proven to be able to influence business performance. However, digital payments are not able to moderate the influence of intellectual capital on business performance. Keywords: Intellectual Capital, Digital Payment, Business Performance